Bio-recovery of silver from simulated silver electroplating wastewater using palm (Elaeis guineensis) leaves extract / Ahmad Arif...[et al.] - Arif, Ahmad; Jai, Junaidah; Ahmad Zamanhuri, Norashikin
In this research, the role of an eco-friendly biomaterial, palm (Elaeis guineensis) leaves extract as a reducing and stabilizing agent to recover precious metal silver from simulated silver electroplating wastewater, was studied. The phytochemical compounds present in the palm leaves extract, which possesses antioxidant properties, were characterized according to their functional groups and the parameters involved in affecting the silver bio-recovery effectiveness were investigated. The studies found that major types of phytochemical compounds that assist silver bio-recovery were polyphenols, alcohols, carboxylic acid and reducing sugars. Meanwhile, the parameters of reactant's concentration ratio, acidity and metal impurities were found to absolutely affect the silver bio-recovery effectiveness. The characterization of the recovered suspended solid particles after the bio-reduction process reveals that silver metals with high degree of crystallinity were successfully recovered and in nano-sized.